A case of phenobarbitone induced Stevens-Johnson syndrome-toxic epidermal necrolysis along with its causality assessment - Singh, Rohit K.; Rani, Rakhi; Shankar, Vikas; Sinha, Rani I. (International Journal of Basic & Clinical Pharmacology, 2022)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse drug reaction, which are mainly caused by drugs; and these are usually associated with high degree of morbidity and mortality. They are characterized by mucocutaneous tenderness and typically haemorrhagic erosions, erythema and more or less severe epidermal detachment as blisters and areas of denuded skin. High risk drugs for the development of SJS-TEN include phenobarbitone, phenytoin, carbamazepine, lamotrigine, nevirapine, NSAIDs, allopurinol, and cotrimoxazole. A 33 years old female patient came to skin and venereal diseases (VD) outpatient department (OPD) with complaints of painful skin lesions. She was apparently symptom free 15 days back. Then she took tablet phenobarbitone 60 mg, BD as her anti-epileptic treatment. After 12-13 days of taking the drug, she developed erythematous papules associated with itching over her both forearm, face, chest, abdomen, back and lower limbs bilaterally which rapidly progressed to fluid-filled blisters that ruptured to form painful erosions and desquamation of skin all over the body. The patient was managed by withdrawal of phenobarbitone and conservatively, and the patient recovered successfully. The causality of phenobarbitone in this reaction was “probable” as per Naranjo scale. Seriousness of the reaction was “prolonged hospitalization”. Phenobarbitone is one of the most common causative agents of SJS and TEN. The main stay of treatment is immediate withdrawal of causative agent along with supportive care.